Cooperation under democracy and authoritarian norms - Björn Vollan; Yexin Zhou; Andreas Landmann; Biliang Hu; Carsten Herrmann-Pillath (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2013)
There is ample evidence for a "democracy premium". Laws that have been implemented via election lead to a more cooperative behavior compared to a top-down approach. This has been observed using field data and laboratory experiments. We present evidence from Chinese students and workers who participated in public goods experiments and a value survey. We find a premium for top-down rule implementation stemming from people with stronger individual values for obeying authorities. When participants have values for obeying authorities, they even conform to non-preferred rule. Our findings provide strong evidence that the efficiency of political institutions depends on societal norms.
Keywords: A13; C92; D02; D72; H41; 330; Deterrent effect of legal sanctions; expressive law; authoritarian norms; public goods; democratic voting; China; Öffentliche Güter; Soziale Norm; Institutionelle Infrastruktur; Autoritäres System; China